(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
The purpose of this study was to determine if adifference in achievement scores exist between students who attended the SchoolSystem preschool program and those who did not as measured by standardizedachievement test Reading/Language Arts and Math scores of students in the thirdand fourth grades. The variables of grade level and preschool attendance wereconsidered. The population consisted of students who were in the third orfourth grades in the School System during the 2010-2011 school years throughthe 2012-2013 school years. Independent and paired t-tests were used toevaluate differences in the variables. The investigation of the relationshipbetween attendance in preschool and achievement test scores might assisteducators in planning and implementation of future preschool programs withinthe public school setting.